Wind tunnel investigation of horizontal and vertical sand fluxes of ascending and descending sand particles in aeolian sand transport. Issue 12 (6th April 2016) - Kang, Liqiang; Zou, Xueyong; Zhao, Guodan; Zhang, Chunlai; Cheng, Hong
Abstract: The horizontal and vertical sand mass fluxes in aeolian sand transport are investigated in a wind tunnel by PTV (particle tracking velocimetry). According to the particle velocity and volume fraction of each individual particle from PTV images, the total horizontal sand mass flux, the horizontal mass fluxes of ascending and descending sand particles, and upward and downward vertical sand fluxes are analyzed. The results show that the horizontal mass fluxes of ascending and descending sand particles generally decrease with the increase of height and can be described by an exponential function above about 0.03 m height. At the same friction velocity, the decay heights of the total horizontal sand mass flux and the horizontal mass fluxes of ascending and descending sand particles are very similar. The proportion of horizontal mass flux of ascending sand particles is generally about 0.3–0.42, this means the horizontal mass flux of descending sand particles makes an important contribution to the total horizontal sand mass flux. Both the upward and downward vertical sand mass fluxes generally decrease with height and they are approximately equal at the same height and friction velocity. The relation between upward (or downward) vertical sand mass flux and horizontal sand mass flux can be described by a power function. The present study is used to help understand the transport of ascending and descending sand particles. Copyright © 2016 John Wiley & Sons, Ltd.